Acquisition of plasmids conferring carbapenem and aminoglycoside resistance and loss of surface-exposed macromolecule structures as strategies for the adaptation of Acinetobacter baumannii CC104O/CC15P strains to the clinical setting - Cameranesi, María Marcela (2020)
Fil: Fil: Cameranesi, María Marcela. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Biología Molecular y Celular de Rosario (IBR -CONICET); Argentina.